Use of a LiESP/QA-21 vaccine (CaniLeish) stimulates an appropriate Th1-dominated cell-mediated immune response in dogs. - Javier Moreno; Ioannis Vouldoukis; Virginie Martin; David McGahie; Anne-Marie Cuisinier; Sylvie Gueguen (Public Library of Science (PLoS), 2012)
Canine leishmaniasis is an important zoonotic disease of dogs. The clinical outcome of infection is variable, with the efficiency of the immune response being the key determining factor. There is now a general consensus that a predominant Th1 immune profile in an overall mixed Th1/Th2 response is associated with resistance in dogs, and the absence of a strong Th1 influence is associated with a progression to clinical disease. As a result, there has been a growing demand for vaccines that can induce a specific, strong Th1 response. In this study, we measured the impact of a primary course of a newly available LiESP/QA-21 vaccine on selected humoral and cellular markers of the canine immune response during the onset of immunity. All vaccinated dogs developed a humoral response characterised by IgG2 production. More importantly, vaccinated dogs developed significantly stronger cell-mediated immunity responses than did control dogs. Vaccination induced specific cellular reactivity to soluble Leishmania antigens, with a Leishmania-specific lymphoproliferation (p = 0.0072), characterised by an increased population of T lymphocytes producing IFN-γ (p = 0.0021) and a significant ability of macrophages to reduce intracellular parasite burdens in vitro after co-culture with autologous lymphocytes (p = 0.0014). These responses were correlated with induction of the NOS pathway and production of NO derivatives, which has been shown to be an important leishmanicidal mechanism. These results confirm that vaccination with LiESP/QA-21 induces an appropriate Th1-profile cell-mediated response within three weeks of completing the primary course, and that this response effectively reduces the parasite load in pre-infected macrophages in vitro.